TEACHING TERMINOLOGICAL WORDS IN THE LANGUAGE FOR SPECIAL PURPOSES (Conferencea, 2023)
The article considers some ways of teaching terminological units to the students of non-philological universities on the example of terminological phrases of the scientific and technical field "Construction" in the special vocabulary of English language.